Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

Consider the following problem

I pull a mass m resting at x = 0 on a frictionless table connected to a spring with some k by an amount A and let it go. What will be its speed at x=0?

I know how to solve it using the law of energy conservation but as a challenge I wanted to find the solution without it.

So from the 2nd Newton's law it's obvious that a = k*x/m. But I don't know how to integrate it in order to find velocity since a = f(x(t)).

How would I solve this without using the law of energy conservation?

share|improve this question
1  
Your system is a harmonic oscillator. Have a look at en.wikipedia.org/wiki/Harmonic_oscillator and if you run into problems with the maths ask again here. –  John Rennie Oct 26 '12 at 8:08

2 Answers 2

up vote 0 down vote accepted

I believe you could use some differential calculus.
A helpful formula is a = d(v^2 / 2)/dx, derived via a = dv/dt = dv/dx * dx/dt

$$a = {-kx \over m}$$ $$a = {\operatorname{d}\!({1 \over 2}v^2)\over\operatorname{d}\!x}$$ $$\therefore -{1 \over 2}v^2 = \int {k \over m} x dx = {k \over 2m}x^2+c$$ When $x=A$, $v=0$: $\therefore c = +{kA^2 \over 2m}$ $$\therefore v = +\sqrt{{-kx^2+kA^2 \over m}}$$ When $x=0$, $v=\sqrt{{kA^2 \over m}}$

This is the same result as that you would get using energy.

(I've assumed that the force causing the spring to retract is F = -kx.
I've made this assumption based on it being the force required to stretch the string at constant velocity)

share|improve this answer

If you know $a(x)$ then use the following formulas ( derived from $a = \frac{{\rm d}v}{{\rm d}x} v$ )

$$ \frac{1}{2} v(x)^2 = \int a(x)\,{\rm d}x + C_1 $$

$$ t = \int \frac{1}{v(x)}\,{\rm d}x + C_2 $$

where the constants $C_1$ and $C_2$ are found from the initial conditions.

Example:

$a(x)=-\frac{k}{m} x$

$$ \frac{1}{2} v(x)^2 = \int \text{-}\frac{k}{m} x \,{\rm d}x + C_1 = \frac{k\, (A^2-x^2)}{2\,m} $$ for $v=0$ at $x=A$. The above is inverted to

$$ v(x) = \sqrt{ \frac{k\,(A^2-x^2)}{2 m} } $$

The solution is then $v(0) = \sqrt{ \frac{k\,A^2}{2 m} } $

The time is more complex to get

$$ t = \int \frac{1}{v(x)}\,{\rm d}x + C_2 = C_2 + \int \frac{ \sqrt{ \frac{m}{k} } }{ \sqrt{A^2-x^2} } \,{\rm d}x = \sqrt{ \frac{m}{k}} \left( \arccos\left(\frac{x}{A}\right) \right) $$

for $x=A$ at $t=0$. This is inverted for

$$ x(t) = A \cos\left(\sqrt{\frac{k}{m}}\,t\right) $$

share|improve this answer
    
I just found this great link that does exactly this: CodeCogs/Reference –  ja72 Oct 26 '12 at 17:49

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.